2017
DOI: 10.1159/000454802
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarker-Based Diagnosis of Sporadic Creutzfeldt-Jakob Disease: A Validation Study for Previously Established Cutoffs

Abstract: Background: Several biomarkers have been proposed to discriminate sporadic Creutzfeldt-Jakob disease (sCJD) from other dementias and control cases. However, their clinical accuracy depends on the PRNP codon 129 genotype, leaving it unclear how well established markers behave in untested conditions. Methods: We analyzed 14-3-3, tau, p-tau levels, and the p-tau/tau ratio in a population sample collected from Polish hospitals including nondementia, dementia, and definite sCJD cases and validated their parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
5
17
0
Order By: Relevance
“…Another relevant finding from our study is the potential prognostic value displayed by NFL in sCJD cases, since their levels were negatively correlated with disease duration, as it was previously shown in other dementia-types, especially in AD [2]. Other prion biomarkers such as tau and -synuclein also show a prognostic value for sCJD cases [36,50,51], while data for 14-3-3 [52,53] and RT-QuIC [49,54] are inconsistent.…”
Section: Elevated Nfl Concentrations In Vad and Ftd Were Also In Agresupporting
confidence: 59%
“…Another relevant finding from our study is the potential prognostic value displayed by NFL in sCJD cases, since their levels were negatively correlated with disease duration, as it was previously shown in other dementia-types, especially in AD [2]. Other prion biomarkers such as tau and -synuclein also show a prognostic value for sCJD cases [36,50,51], while data for 14-3-3 [52,53] and RT-QuIC [49,54] are inconsistent.…”
Section: Elevated Nfl Concentrations In Vad and Ftd Were Also In Agresupporting
confidence: 59%
“…The 14‐3‐3 proteins are highly expressed in the brain and some of the 14‐3‐3 isoforms are particularly enriched in the presynapses, to regulate transmission and plasticity . The 14‐3‐3 γ protein presents increased levels in the CSF of sporadic CJD and is accepted as part of the current diagnostic criteria . YKL‐40 is a glycoprotein produced by inflammatory cells, mostly astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that total‐Tau concentrations correlate with disease duration in CJD cases . When allowing for nonlinear associations between t‐Tau and Non‐P‐Tau concentrations and disease duration (time between disease onset and death of the patient), Non‐P‐Tau was able to explain more of the variability in disease duration ( r 2 = 0.19) than total‐Tau ( r 2 = 0.11) in 47 CJD cases were information about disease duration was available.…”
Section: Resultsmentioning
confidence: 96%